Cultural Communication 2.0 in Ibero-America: Effectiveness of Government Communication on YouTube - Martínez-Sala, Alba-María (2024)
Culture and national identity are key aspects of the social and economic development of a country. Consequently, cultural communication promotes the processes linked to artistic activities and cultural manifestations that allow preserving the values of a nation and contribute to human and social development, creating a full awareness of the importance of cultural diversity at local, national, and international levels. This article, based on a descriptive-correlational study, evaluates and compares the effectiveness of governmental communication on YouTube about culture in the 19 Ibero-American countries that have a channel on this platform. The communication 2.0 index is used for this purpose (Altamirano-Benítez et al., 2018a; Túñez-López et al., 2016). The results reveal a scarce use of the potential of this channel as a tool for the promotion and dissemination of culture that increases in 2020 compared to 2019. This translates into limited engagement levels. It can be concluded that, for the most part, the organizations analysed should rethink their digital cultural communication strategies to contribute to their objectives regarding the protection and reinforcement of their cultural identity and their tangible and intangible heritage.